Spatial, Temporal, and Interchannel Image Data Fusion for Long-Distance Terrestrial Observation Systems. (12th February 2008) - Fishbain, Barak; Yaroslavsky, Leonid P.; Ideses, Ianir
Abstract : This paper presents methods for intrachannel and interchannel fusion of thermal and visual sensors used in long-distance terrestrial observation systems. Intrachannel spatial and temporal fusion mechanisms used for image stabilization, super-resolution, denoising, and deblurring are supplemented by interchannel data fusion of visual- and thermal-range channels for generating fused videos intended for visual analysis by a human operator. Tests on synthetic, as well as on real-life, video sequences have confirmed the potential of the suggested methods.